Digitalisasi Pemasaran Potensi UMKM Desa Mungkung Kabupaten Nganjuk Melalui Peta Digital Tahun 2024 - Hendra Maulana; Kurnia Rafif Shanika; Laksamana Zulfikar Satria Decca Harits; Laycha Nazila Supoyo Putri; Maulidia Zalsa Wicahyo Putri; Sharla Putri Aisha (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
MSME traders in Mungkung Village consist of various businesses such as culinary, fashion, agribusiness and automotive. However, many of them do not understand technological advances, which hinder the economic development of local MSMEs. Some MSMEs do not have a logo or brand and only rely on local consumers. Life in Mungkung Village is still very traditional, Group 01 KKNT MBKM is aware of this backwardness and is trying to change it. Therefore, researchers intend to advance Mungkung village so that the village community is technologically literate. This research will focus on digitizing the marketing potential of Mungkung Village MSMEs through digital maps to increase their presence and accessibility. The author uses descriptive qualitative research methods with the concepts of digitalization and marketing. This concept is relevant to what the author is researching. The result of this research is that the author succeeded in increasing the potential of MSMEs in Mungkung village by creating a digital map of MSMEs which can be accessed via an online platform. This program also supports SDGs goal point 8, which relates to decent work and economic growth, by empowering MSMEs.